The Effectiveness of the Application of the Kumon-Based English Learning Model to Improve Student Reading Ability - Oktariyani O; Oktariyana O (LPPM STKIP Kusuma Negara, 2020)
The purpose of this study was to determine the effectiveness of the application of Kumon-based English reading learning models compared with conventional methods of English reading skills of PGSD students and Management classes at Trilogy University 2018/2019 school year. This study uses a post-test-only control group design. The focus under study is the process and learning outcomes of students' reading comprehension (cognitive) results. This research uses documentation, observation, and test data collection techniques and analyzed with percentage descriptive techniques, and statistical tests. The ability of experimental class students viewed from the overall learning process is more capable (73.3%) compared to the control class (70%). Based on the percentage of students' post-test results, the control class obtained a percentage of (86.9%) in the excellent category, while in the control class the percentage of post-test scores was (68.33%) in the sufficient category. Thus the Kumon-based learning model is effective in improving students' reading ability in English both in terms of process and results compared to conventional methods.